Halal compliance priority assessment using analytic hierarchy process (AHP) for food service / Ahmad Rusydi Razak - Razak, Ahmad Rusydi (2018)
One of the emerging and lucrative areas is the establishment of halal supply chain management, in particular the food supply chain management. The demand towards an effective and acceptable food management services is quality and compliance to meet the requirement of halal products, in particular, the halal food and beverage supplies across the world. The halal food chain is one of the leading industries that aggressively adapting to newly emerging consumer interests like food safety, animal welfare and convenience in cooking and eating. Problems in tracing the authenticity and allocate the source of contamination always delimits the efficacy of the halal food supply chain management system. To date, very little studies look into the global halal food supply chain management performances. The past studies on tracking movement of imported food (processed) products, reveals a critical level of noncompliance among halal logistics operators. In extension, this study aims to determine criteria of behavior among halal food supply chain management players. The study used analytic hierarchy process (AHP) in determining halal food supply chain parameters (HSCP). The HSCP based approach will analyze continuous logistics process of the supply chain covering outbound and inbound activities and provides the conceptual elements for the assessment of the halal food industry concerns. This study attempts to provide insights to factors that influence decision makers into participating in halal supply chain. Surveys and exclusive interviews with customers, restaurant owners and the food suppliers were conducted over a period of two years in 2014 and 2015. This study discovers some priorities among the two parties involved by intergrating the expectaion of the customers, and conclude that knowledge on halal is second most prioritize by all beside practices and activites, while ingredients is the least prioritize. Thus, it is proposed that creating awareness on various issues related to halal standard, halal certification and halal recognition should be done to improve the acceptance and participation as to assure the dynamism of the halal food supply chain management and the industry, in general.